Pengaruh Etika Kerja Islami dan Kualitas Pelayanan Pedagang terhadap Kepuasan Pelanggan di Pasar PON Jombang - Difa Azzahrowani, Ilma; Rachma Indrarini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The market is a certain place for the meeting of people who carry out trading activities (buying and selling) of goods and services. Jombang is an area that has the nickname as "Santri City", which in accordance with the expectations of the nickname is the creation of the behavior of a good trader and away from bad deeds and will affect satisfaction. However, not all traders in the market reflect this, there are several influencing factors, namely Islamic work ethics and service quality. The application of good work ethics in Islam is very important, because in it will create muamalah activities that are maslahah. Thus, this study aims to analyze the effect of Islamic work ethics and the quality of merchant services on customer satisfaction in the Pon Jombang market. The research method used is descriptive quantitative research with multiple linear regression analysis with SPSS 25 analysis tools. The sample used was 100 respondents through a questionnaire with predetermined criteria. The results of the study state that there is an influence of Islamic work ethics and service quality on customer satisfaction. This research is expected to be able to bring benefits to readers in order to add insight and traders are able to apply Islamic law in buying and selling activities.